Isolation and Identification of Endophytic Fungi from Srikaya Plants (Annona squamosa) Having Potential Secondary Metabolites as Anti-Breast Cancer Activity - PRASETYAWAN YUNIANTO; SYOFI ROSMALAWATI; INDRA RACHMAWATI; WAHYUDI PRIYONO SUWARSO; WAHONO SUMARYONO (Indonesian Society for microbiology, 2012)
Annonaceous acetogenin was extracted from Annona squamosa (Srikaya) seeds. It has cytotoxic activity against cancer cells and lower toxicity compared to other cancer drugs. Endophyte from Annonaceae is expected to have similar extracted metabolites to the host, thus increasing the economic value. This research is a preliminary study to obtain active compounds with potential as anti-cancer agents from endophytic fungi of Srikaya plants. Four endophytic fungal strains were isolated from Srikaya plants (Annona squamosa) and identified based on 28S rDNA sequence. The isolates are SKY II.3.1, SKY I.1.2, SKY II.3.2, and SKY III.3.1, and have similarity with Fusarium sp Vega760, Fusarium sp NRRL 22354 NRRL223, Nectria rigidiuscula, and Fusarium sp BOL35, respectively. The identified isolates were fermented in liquid media for three weeks. The liquid and mycelium were extracted using ethyl acetate. Whole extract of each fermented isolate was partitioned and evaporated to obtain ethyl acetate extract. Cytotoxicity assay of ethyl acetate extract was carried out at level 100 ppm by Methyl Thyazole Tetrazolium (MTT) viability test towards MCF-7 (breast cancer cell). The result indicated that each ethyl acetate extract could inhibit the viability of cell MCF-7 with 11.34, 99.78, 91.48, and 96.84%, for SKY II.3.1, SKY I.1.2, SKY II.3.2, and SKY III.3.1, respectively. Based on the results of cytotoxicity assay on MCF-7 breast cancer cells, endophytic fungi isolates SKY I.1.2, SKY II.3.2, and SKY III.3.1 are potential as sources of anti-breast cancer compounds.